Diversity Management on Workplace Performance and Productivity: A Comprehensive Analysis (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2025)
Globalization and technological progression foster organizations to become multicultural and diversified. Organizations witness an increasing multiplicity of workforce diversity. Age, gender, educational background, mother tongue, languages spoken and written, food preferences, culture, religion, celebrations, values, and beliefs are some of the aspects of diversity that exist. The current study explored the potential effects of workplace diversity on employee’s performance. Specifically, the study aimed to establish the extent of demographic diversity, the degree of socio-cultural diversity, and how the management of workforce diversity affects organizational effectiveness. The study has been done by literature review on the concepts of workforce diversity management, job satisfaction, productivity, and their interrelationships. Based on the findings, the study concludes that diversity management is a process intended to create and maintain a positive work environment where individual similarities and differences are valued. The study suggested that organizations should design and implement customized diversity programs that meet the specific needs of staff members, departments, or the entire company. Additionally, it was proposed that job applicants should receive fair treatment in hiring and advancement, based on their skills rather than subjective characteristics such as color, religion, national origin, gender, age, sexual orientation, or physical disability.